Hubungan Pengetahuan Dan Perilaku Orangtua Dengan Faktor Resiko Terjadinya Pneumonia Pada Balita Di RSUD Jayapura - Nona Mulyani Aronggear (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Pneumonia is an acute respiratory infection that affects the lung tissue (alveoli) (Afriani, A & Oktavia, L, 2021). The toddler years are a phase that is very vulnerable to health problems. Meanwhile, pneumonia is in second place by presentation (15.5%). The factors related to the incidence of pneumonia in children under five are determined from the characteristics of the mother, factors in children under five, nutritional status of children under five and the last factor is environmental factors (Ministry of Health of the Republic of Indonesia, 2018). This research itself uses quantitative methods with observation, distribution of questionnaires and literature reviews so that it can be concluded that the close relationship between parental knowledge, behavior and factors that cause pneumonia in toddlers is significantly related to the expansion of the number of pneumonia in toddlers in RSUD. Jayapura.